Iowa RBA, September 16, 1996 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for September 16, 1996. Highlights of the update include sightings of Snowy Egrets, Little Blue Herons, and a Red-necked Phalarope. Other interesting observations include a Ringed Turtle-Dove, 14 species of Warblers, and 11 species of raptors, including a Red-Shouldered Hawk. Also included are handwritten notes for the next week's update with sightings of Black-throated Blue Warblers and a Yellow Rail, as well as notes from an IOU field trip to Snake Creek State Game Management Area. Epson - sheet feed/flatbed